DC Smart Grid Connected with Fuel Charging Station and AC Load by Hybrid MLI - Naveen Kumar (Institute of Advanced Engineering and Science, 2013)
This paper presents the Solar (photo voltaic) power Plant and Windmill plant with DC Smart Grid connected with an DC Fuel Charging Station For Electric Vehicle (EV), Plug in Hybrid Electric Vehicle (PHEV) and converted to AC load for Consumer single or Three phase ac load by means of Hybrid Multilevel Inverter (MLI). Solar Energy which store energy in lithium-ion battery and connected to Smart Grid .Wind Energy which get stored in Lithium-ion battery that Fixed DC Voltage connected with DC Smart Grid. Smart Grid which are Connected with DC Fuel Charging Station in Ring Topology with a certain distance for charging of Electric Vehicle (EV) and Plug-in Hybrid Electric Vehicle with On-Board (Integrated) Charger for faster charging of EV. In Power demand for Consumer the DC load from smart grid converted into an ac load by Hybrid Multilevel Inverter. In Consumers Place the small wind mill and PV panel are installed that energy can be used for consumers load at peak time or power Shutdown .Other than the power shutdown or peak time in the consumers place, stored DC Energy can be fed to Smart Grid. A major development in distribution automation is deployment of smart meters as a gateway between the utility and customer. With such capabilities the smart meter becomes not only a point of measurement of consumed kWh but also a controller capable of bidirectional communications with both the customer and utility.DOI: http://dx.doi.org/10.11591/ijpeds.v3i3.3884